Economies of driftwood: Fuel harvesting strategies in the Kodiak Archipelago - Shaw, Jennie (Études/Inuit/Studies)

(untitled) (Association Inuksiutiit Katimajiit Inc., 2012)
AbstractFuelwood harvesting is an integral part of the subsistence regime for many Arctic and subarctic peoples. Despite the relative paucity of woody resources in the northern tundra, charred wood fragments recovered from archaeological sites reveal a harvesting practice that is thousands of years old. Indeed, fuelwood gathering is a strategic behaviour involving a complex set of decisions beyond merely harvesting by proximity, as some have proposed. In this research, fuelwood harvesting is modeled within an economic framework. A fuel value index (FVI) is established to quantify the energetic returns of different wood species, and ethnographic interviews with Kodiak Island residents demonstrate the knowledge context that surrounds firewood acquisition. Archaeological charcoal from Kodiak Archipelago sites showcases a flexible, though increasingly selective strategy of fuelwood use by early inhabitants. For 7,500 years, maritime hunter-gatherers in the Gulf of Alaska took advantage of wood patchiness; they used a combination of exotic coniferous species in the form of driftwood and native deciduous trees such as alder to fuel their steam baths, smokehouses, and homes.